Quantum dot scanning tunneling microscopy for Majorana bound states in continuum - Zhang, Hai-Rui; Sun, Yong-Ping (Frontiers in Physics, 2022)
We propose a device composing of a quantum dot (QD) connected to a normal mental lead to detect the Majorana bound states (MBSs), which are formed at the ends of a topological superconductor nanowire (TSNW) and coupled to the lead with spin-dependent hybridization strengths. The information of the MBSs leaked into the lead is inferred from the spectral function of the QD servicing as the tip of a scanning tunnelling microscopy (STM). It is found that lead-MBSs interaction induces a bound state characterized by an infinitely-high peak in the dot’s zero energy spectral function. The overlap between the two modes of the MBSs turns this bound state into a resonant one, and thus the zero-energy peak is split into three with the height of the central one equals to that in the absence of lead-MBSs coupling. We also find that the MBSs have less impacts on the additional peak in the dot’s spectral function induced by intradot Coulomb interaction.